Applying Muslim-friendly tourism principles in destination management: Evidence from Aceh, Indonesia - Adinugraha, Hendri Hermawan; Al-Kasyaf, Muhammad Zheeva; Nasaruddin, Razie Bin (International Journal of Halal Industry, 2025)
Purpose – This study describes and analyzes the implementation of Muslim-Friendly Tourism (MFT) principles in managing tourist destinations in Aceh, Indonesia. Methodology – This research uses a qualitative approach with a case research method, collecting data through in-depth interviews, direct observation, and document analysis. Findings – The results showed that implementing MFT principles in Aceh still faces challenges, such as limited worship facilities, suboptimal halal certification in the culinary and accommodation sectors, and a lack of local community involvement in destination management. Nevertheless, applying Sharia law in Aceh is a strong asset for strengthening the halal tourism ecosystem. Local governments, tourism businesses, and communities play a strategic role, but stakeholder coordination still needs improvement. The availability of Sharia-based services strongly influences Muslim traveler satisfaction and directly affects traveler loyalty. Implications – The implications are to design a more inclusive and sustainable halal tourism development strategy for policymakers. This research emphasizes the importance of synergy between the government, business actors, and the community in strengthening Aceh’s competitiveness as a global halal tourism destination. Originality – This research enriches the literature on halal tourism and provides strategic recommendations for the more effective management of Sharia-based destinations.